IgA in alcoholic cirrhosis. - Kalsi, J (1983)
Circulating IgA in patients with alcoholic cirrhosis was quantitated and characterized to determine the proportion of monomer and dimer present. Polymeric (p) IgA formed a significantly greater proportion of the total serum IgA in cirrhosis, but these individuals showed significant elevations of serum levels of monomeric (m) as well as pIgA. Thus a selective disturbance of pIgA metabolism could not entirely account for the abnormal serum IgA levels. Studies on spontaneous IgA synthesis in vitro by peripheral blood lymphocytes showed that greater amounts of both mIgA and pIgA were formed by cells from patients with cirrhosis compared with control individuals.